Promoting adab and honesty: responsible content creation for KICTzens' tiktok - Zainuddin, Ahmad Anwar; Md Nor, Nor Saadah; Kamarul Zaman, Nur Anis Sofea; Mohd Razali, Muhammad Irfan Zaki (Kulliyyah of Information and Communication Technology, IIUM, 2023)
KICTzens’ TikTok page is a platform that should follow Islamic norms of modesty and decency, suitably covering the 'aurah' in accordance with Shariah guidelines.